Genetic polymorphism and population structure of Torghut Mongols and comparison with a Mongolian population 3000 kilometers away. (September 2019) - Wu, Riga; Li, Ran; Wang, Nana; Peng, Dan; Li, Haixia; Zhang, Yinming; Zheng, Chenghao; Sun, Hongyu
Highlights: Both the Torghut and Jalaid Mongols have population-specific alleles. The STRs and SNPs analyzed here could be employed in forensic applications. The Torghut and Jalaid Mongols are closely related by their genetic background. Interpopulation comparisons revealed genetic differences between the two populations. Abstract: Mongolians played a pivotal role in shaping the culture and genetic architecture of modern Eurasia through the rapid expansion of the Mongol Empire in the 13th century. While the historical aspects of the Mongolian Empire are well documented, research on the genetic variations among Mongolian populations is still insufficient. In this study, we examined the genetic diversity of 70 Torghut Mongols residing in the Ili region of China compared with 88 Jalaid Mongols residing 3000 km away. Over 200 forensically relevant genetic markers, including autosomal short tandem repeats (A-STRs), X chromosomal STRs (X-STRs), Y chromosomal STRs (Y-STRs), identity-informative single nucleotide polymorphisms (iiSNPs), ancestry-informative SNPs (aiSNPs), and phenotype-informative SNPs (piSNPs), were genotyped to uncover the genetic polymorphism of the Torghut Mongols. The STR genotyping results showed that 80 alleles (39 A-STRs, 25 Y-STRs, and 16 X-STRs; 14.4% of 554 alleles) identified in Torghut Mongols were not identified in Jalaid Mongols, while 155 alleles (84 A-STRs, 59 Y-STRs and 12 X-STRs; 24.6% of 630 alleles) identified in Jalaid Mongols were not observed in Torghut Mongols. Calculation of the forensic parameters demonstrated that the STRs and SNPs analyzed here could be employed in forensic applications. Interpopulation comparisons via principal component analysis (PCA), phylogenetic tree, and STRUCTURE analysis showed that the two Mongolian populations were closely related by their genetic background, although genetic differences were also discovered. When both the sequence-based A-STRs and iiSNPs were included in the STRUCTURE analysis, the Torghut population was more similar to the Uyghur population than to Jalaid Mongols, indicating certain population structure differences between the two Mongolian populations. The Y-DNA haplogroup prediction showed that although haplogroup C (C2-M217) was dominant in both Mongolian populations, haplogroup O2-M122 was rarely presented in Torghut Mongols, which differentiated the Torghut Mongols from the other Mongolian populations. This study not only uncovered the genetic features of the two Mongolian tribes, providing valuable frequency data for forensic applications, but the genetic patterns of the two Mongolian populations also provide a genetic evidence that the Torghut Mongols may have developed via the gradual intermixing of nomadic groups of Mongol and Turkic origin, as recorded in historical records. This study also highlighted the importance of building regional reference databases that consider both ethnic and geographic location information, instead of a more universal reference database, for forensic applications.